2021
DOI: 10.3389/feart.2021.680865
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Seismicity During a Stalled Episode of Reawakening at Cayambe Volcano, Ecuador

Abstract: Cayambe Volcano is an ice-capped, 5,790 m high, andesitic-dacitic volcanic complex, located on the equator in the Eastern Cordillera of the Ecuadorian Andes. An eruption at Cayambe would pose considerable hazards to surrounding communities and a nationally significant agricultural industry. Although the only historically documented eruption was in 1785, it remains persistently restless and long-period (LP) seismicity has been consistently observed at the volcano for over 10 years. However, the sparse monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 110 publications
2
8
0
Order By: Relevance
“…1a). Recently, Butcher et al (2021) have attributed this seismic crisis to the internal motion of hydrothermal fluids set off by the ascent of a new magma batch, which was initiated by a change in the static stresses following the Pedernales earthquake. Notably, the last volcanic eruption that affected Cayambe city was that of El Reventador volcano on 3 November 2002.…”
Section: Case Study: the City Of Cayambementioning
confidence: 99%
“…1a). Recently, Butcher et al (2021) have attributed this seismic crisis to the internal motion of hydrothermal fluids set off by the ascent of a new magma batch, which was initiated by a change in the static stresses following the Pedernales earthquake. Notably, the last volcanic eruption that affected Cayambe city was that of El Reventador volcano on 3 November 2002.…”
Section: Case Study: the City Of Cayambementioning
confidence: 99%
“…It has the scientific advantage of clarifying which elements of precursory behaviour can quantitatively be transferred among similar volcanoes. Thus, deterministic reasoning can take advantage of the scale-independent features of fracturing to investigate in the laboratory how precursory behaviour changes under a range of stress histories broader than those covered by available field data; to extrapolate trends to different timescales in the field-for instance, connecting patterns typically seen at intervals of a year or less to those evolving over years to decades (De la Cruz-Reyna et al 2008;Parks et al 2012;Robertson and Kilburn 2016;Kilburn et al 2017;Stix 2018;Bell et al 2021); and to use rates and durations of signals to seek distinctions between pre-eruptive and intrusive unrest (Sturkell et al 2003;White and McCausland 2019), between magmatic and hydrothermal pressure sources (Pritchard et al 2018;Sandri et al 2019) and even between styles of eruption (Cassidy et al 2018).…”
Section: An Integrated Frameworkmentioning
confidence: 99%
“…With the growth of machine learning and artificial intelligence, new opportunities are emerging for revealing mutual dependencies among a broader range of precursors at both frequently and rarely erupting volcanoes (Anantrasirichai et al 2019;Gaddes et al 2019;Sun et al 2020;Carniel and Guzmán, 2021). Physics-based procedures are thus well placed to advance quantitative analyses of (1) additional physical precursors and their causes, such as long-period earthquakes, tremor and seismic b value (McNutt 1996(McNutt , 2005Chouet and Matiza 2013;Bean et al 2013;Roberts et al 2015;Chardot et al 2015;Dempsey et al 2020;Butcher et al 2021);(2) relations between the composition and flux of volcanic gases and the physical state of subsurface magma (Chiodini et al 2016;Liu et al 2020;Moretti et al 2020;Raponi et al, 2021);(3) connections between observed patterns of unrest and those expected from numerical models of magmatic processes (NASEM 2017); (4) forecasts of the likely size and style of an eruption (Tazieff 1979;White and McCausland 2019); and (5) forecasts of eruption and changes in eruptive behaviour at frequently erupting and open-system volcanoes (Brancato et al 2011;Carrier et al 2015;Bell et al 2017;Neuberg et al 2018;Gaunt et al 2020). All these goals are within our grasp and a test of progress in the next 20 years will be how far we have transformed today's uncontrolled volcanic experiments into tomorrow's forecastable events.…”
Section: Looking Forwardmentioning
confidence: 99%
“…In this period, 2300 earthquakes were recorded, the highest number of events recorded at Cayambe since seismic monitoring began in the late 1980s. According to Butcher et al (2021), the June swarm was associated with a reactivation of the regional Chingual fault system.…”
Section: Cayambe Volcano Tecto-volcanic Context and Recent Eruptive A...mentioning
confidence: 99%
“…The combination of an increasing amount of SAR data and improved processing methods is expected to favor subtle signal detection and analysis particularly in such vegetated and topographically active areas as the Andes. Here, we test this new potential by studying surface deformation patterns at Cayambe volcano, in northern Ecuador, which experienced a recent seismic crisis (Butcher et al 2021).…”
Section: Introductionmentioning
confidence: 99%